2021
DOI: 10.1002/cmdc.202100406
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Highly Potent and Specific ABHD6 Inhibitors

Abstract: Fine‐tuning than complete disruption of 2‐arachidonoylglycerol (2‐AG) metabolism in the brain represents a promising pharmacological approach to limit potential untoward effects associated with complete blockade of monoacylglycerol lipase (MGL), the primary hydrolase of 2‐AG. This could be achieved through a/b‐hydrolase domain containing 6 (ABHD6) inhibition, which will provide a smaller and safer contribution to 2‐AG regulation in the brain. Pharmacological studies with ABHD6 inhibitors have recently been rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…ABHD6 is a multifunctional enzyme that produces 2‐AG from DAG under basal conditions in N2a cells (van Esbroeck et al, 2019) but hydrolyses 2‐AG in stimulated neurons (Marrs et al, 2010). To test if ABHD6 controls the P2X 7 R‐dependent increase in 2‐AG production in N2a cells, we used its recently developed inhibitor, AM12100 (Figure 6a) (Kokona et al, 2021; Malamas et al, 2021). ABPP analysis showed that AM12100 inhibited ABHD6 activity with an IC 50 = 19 nM and reduced ABHD6 activity by 74% at 30 nM without affecting DAGLβ activity (Figure 6j and Figure S6f,h).…”
Section: Resultsmentioning
confidence: 99%
“…ABHD6 is a multifunctional enzyme that produces 2‐AG from DAG under basal conditions in N2a cells (van Esbroeck et al, 2019) but hydrolyses 2‐AG in stimulated neurons (Marrs et al, 2010). To test if ABHD6 controls the P2X 7 R‐dependent increase in 2‐AG production in N2a cells, we used its recently developed inhibitor, AM12100 (Figure 6a) (Kokona et al, 2021; Malamas et al, 2021). ABPP analysis showed that AM12100 inhibited ABHD6 activity with an IC 50 = 19 nM and reduced ABHD6 activity by 74% at 30 nM without affecting DAGLβ activity (Figure 6j and Figure S6f,h).…”
Section: Resultsmentioning
confidence: 99%
“…However, there are very few studies in the literature pertaining to their role in the retina. Acute treatment with the novel inhibitors of the 2-AG hydrolytic enzymes, AM12100 (ABHD6) and AM11920 (dual MAGL/ABHD6) [63] attenuated the AMPA-induced microglial/macroglial activation (Iba1-IR/GFAP-IR) and produced dosedependent partial neuroprotection, with the dual inhibitor being more efficacious [31]. These results suggest that the pharmacological blockade of the 2-AG hydrolytic enzymes and the subsequent increase in the endogenous 2-AG levels may provide a beneficial therapeutic strategy for neurodegenerative retinopathies.…”
Section: Blockade Of 2-ag Hydrolytic Enzymes: Endogenous 2-ag Actionsmentioning
confidence: 99%
“…Many inhibitors of the ABHD protein family are summarized by Bononi et al ., [62] several of which have been identified through ABPP. Recently, ABPP enabled the discovery of a new ABHD6 inhibitor that improves selectivity over MGL and FAAH [63] …”
Section: Competitive Abpp Screening For Lipid Hydrolase Inhibitor Dis...mentioning
confidence: 99%
“…Recently, ABPP enabled the discovery of a new ABHD6 inhibitor that improves selectivity over MGL and FAAH. [63] In a recent publication on the immunomodulatory lipid networks in innate immune cells, the Cravatt lab used DAGLB inhibitors DO34 and DH376 as well as the MGL inhibitor MJN110 to investigate the activity and contribution of these enzymes in human monocyte-derived macrophages. [6a] They employed competitive ABPP to confirm that these inhibitors work in primary cell lines as well as to rule out off-targets.…”
Section: Competitive Abpp Screening For Lipid Hydrolase Inhibitor Dis...mentioning
confidence: 99%